International trade impact on food security among selected low-middle and low-income countries - Benavidez Hernandez, Lauren Sarid (Kansas State University, 2022)
Food security is a relevant indicator of development and, for years, a topic of discussion for organizations aiming to improve this in developing countries. International trade, on the other hand, has been a tool to facilitate access to foods that a country’s domestic production cannot cover; however, through the literature review about these topics, there has been a debate on whether international trade might, in fact, harm countries’ state of food security. Low-middle and low-income countries have a state of food security that comes from a good to a weak level, according to the Global Food Security Index (GFSI). This thesis aimed to determine whether international trade affects food security and in which direction this impact moves in a set of low-middle and low-income countries. For these, two significant indicators of food security were analyzed: food availability and food affordability. Data from diverse sources was collected to construct variables that were related to countries food supply measured by kilograms and kilocalories and food diet costs ratio to per capita income to measure food affordability. These main measures were analyzed using inferential methods and an econometric model regarding general trade, food, and other trade-related variables. In the case of food availability, the models used were OLS and an Instrumental Variable model obtained from the gravity model of international trade. The methods used for food affordability were a GLS-AR1 model and OLS and IV, models. By-country estimates and panel estimates were obtained for the two factors. For both indicators, it was found that international trade variables do affect both affordability and availability of foods in those countries; however, the direction of these effects was variable among the factors. For food availability, the total trade of merchandise as a percentage of GDP, in most cases, caused a negative impact on food availability, except when analyzing the panel estimates; the effect of food imports and exports was more diverse depending on the country, and more conclusive for food exports in the panel estimates. The negative or positive effect of trade was more pronounced when analyzing the availability through kilocalories, and the created IV proved to have larger estimates. In the case of food affordability, the results were more constant; most trade-related variables were found to cause a diminution in the ratio between diet cost and income, thus, making food affordable. The agricultural tariff was the only variable that negatively affected affordability, but this is expected as tariffs represent a trade barrier. The present research adds to the literature a supporting investigation that, given the data, model, and assumptions made, indicates that the food trade is favorable for those countries in which food security state is critical, principally in affordability factor.
Keywords: International trade; Food security; Availability; Affordability